Analisis Kesalahan Berbahasa pada Bidang Morfologi Terhadap Jual Beli Online di Instagram (The Analysis of Language Error in the Field of Morphology of Online Buying and Selling in Instagram) - Oktavia, Wahyu (Balai Bahasa Jawa Tengah, 2018)
Instagram is an online based communication that frees users to comment with each other. In the analysis of morphological error in the field of morphology of online buying and selling in instagram this. The problem in this reseach are (1) how the form of error in online trading in the field of morphology, (2) what factor become the influence of language error on the sale and purchase in instagram. The purpose of this reseach is (1) to know what form of mistake of language to online sale and selling in morphology field, (2) to know what factors influencing error of language. This research uses qualitative descriptive technique and using observation and documentation method. The result of the analysis of language error on the sale and purchase in the field of morphology that includes errors in the formation of word, errors in spelling and error in capital letter writing. The influencing factors include user language factor, lack of understanding of indonesian language rules, psychological factors, environmental factors, language factors, regional language influence and foreign language influence.Keywords: Language error, Morphology, Online, Instagram